2020
DOI: 10.1016/j.jss.2019.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management and Outcomes After Cesarean Section—A Cross-Sectional Study From Rural Rwanda

Abstract: Background: Cesarean sections (c-sections), the most common surgical procedures performed worldwide, are essential in reducing maternal and neonatal deaths. There is a paucity of research studies on c-section care and outcomes in rural African settings. The objective of this study was to describe demographic characteristics, clinical management, and maternal and neonatal outcomes among women receiving c-sections at Kirehe District Hospital (KDH) in rural Rwanda. Methods: This retrospective cohort study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…This finding is consistent with the study conducted by Rojas et al which demonstrated a significant association of CS with neonatal infection [24]. The intra-operative procedure during CS with a lack of fully sterile conditions might have led to the increased risk of infection [25]. Furthermore, the indications for CS such as fetal distress, cord prolapse, prolonged or obstructed labor contributes to the increased risk for infection [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with the study conducted by Rojas et al which demonstrated a significant association of CS with neonatal infection [24]. The intra-operative procedure during CS with a lack of fully sterile conditions might have led to the increased risk of infection [25]. Furthermore, the indications for CS such as fetal distress, cord prolapse, prolonged or obstructed labor contributes to the increased risk for infection [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with the study conducted by Rojas et al which demonstrated a significant association of CS with neonatal infection [22]. The intra-operative procedure during CS with a lack of fully sterile conditions might have led to the increased risk of infection [23]. Furthermore, the indications for CS such as fetal distress, cord prolapse, prolonged or obstructed labor contributes to the increased risk for infection [24,25].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, similar to the Mazimpaka study, patients 24 and 72 hours after discharge did not have significant post-operative complications. 18 In about our study limitation, we can say that due to COVID-19 pandemic the referral of mother changed from onsite interview to call interview and during this call follow-up we invited women to come to the clinical examination if they had symptoms.…”
Section: Discussionmentioning
confidence: 99%